Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells. Issue 23 (2nd December 2021) - Kim, Mi-Hee; Kwon, Bora; Kim, Kwang-Sang; Kim, Min-Sook; Kim, Min-Ji; Kim, Hwa-Jin; Choi, Da-In; Park, Miyeon; Kim, Moosung; Shin, Min-Kyu; Jeong, Seung-Il; Yu, Kang-Yeol; et al.
Abstract: To enhance the skin whitening effect, tyrosinase activity and melanin biosynthesis needs to be suppressed in the skin. To achieve this goal, we examined the extract of Thymus quinquecostatus flowers, and identified a functional ingredient, galuteolin. Galuteolin effectively inhibited melanin biosynthesis in B16/F10 cells, partially suppressing tyrosinase activity. Therefore, this study suggests that galuteolin can be used as a cosmetic ingredient for skin whitening. Graphical Abstract: